Moderate Islam and women’s empowerment in Indonesia: Institutional transformation, contextual interpretation, and gender justice - Muhammad Nasruddin; Siti Muliana (An-Nisa’ Journal of Gender Studies, 2023)
Moderate Islam is often understood primarily as a counter-discourse to radicalism and conservatism, yet it also provides an important framework for women’s empowerment through Nahdlatul Ulama (NU) and Muhammadiyah, major institutional actors in Indonesia’s moderate Islamic landscape. This study examines patterns of moderate Islam, women’s empowerment initiatives within NU and Muhammadiyah, and the role of moderate Islamic orientations in advancing women’s liberation and gender equality. The study employs a qualitative library research approach, using the interactive qualitative analysis model of Miles and Huberman, source triangulation, and data from books, journal articles, and relevant institutional documents. The findings reveal three interconnected patterns. First, NU and Muhammadiyah demonstrate a shift from the traditionalist–modernist dichotomy toward a more inclusive, dialogical, and maslahah-oriented model of moderate Islam. Second, their women’s organizations promote empowerment through education, advocacy, leadership development, socio-economic initiatives, and gender-responsive Islamic jurisprudence. Third, moderate Islamic approaches grounded in maqāṣid al-sharīʿah support contextual interpretations of Islamic teachings that challenge patriarchal interpretations and religious justifications for violence while affirming gender equality and women’s empowerment. The study concludes that moderate Islam functions not merely as a religious identity but also as an institutional and epistemological framework that connects Islamic normative commitments to women’s empowerment and gender justice. Its contribution lies in linking maqāṣid al-sharīʿah, contextual interpretation, and institutionalized women’s empowerment practices within the Indonesian Islamic context.